Dialogue in religious education - Jerzy Bagrowicz (Nicolaus Copernicus University in Toruń, 2010)
It isn't difficult to notice that contemporary society differs more and more not only in opinions on sociopolitical and cultural issues, but also in religious and denominational aspects. In this pluralistic world dialogue becomes more and more important as a way of communication between people and of making contact and co-operation for the good of the individual human person and society. The dialogue becomes therefore a basic way of building social community. In the second half of the 20th. century began the dialogue between different religions. For over hundred years has continued the ecumenical dialogue between particular Christian denominations. A very important role in the preparation for the dialogue, especially ecumenical and inter-religious dialogue, is religious education: the teaching of different religions and upbringing to dialogical attitude in situations of meeting with people developed in other cultures, worldviews or religions. Efficacy of religious education depends on education in families, schools and other educational communities. It depends on the positive influence of these communities in forming the dialogical attitude. A very important role in this process is religious education in schools as well as in youth religious groups and movements. Taking care of cultural and religious identity of young people shouldn't be any handicap in forming dialogical attitude and preparing for co-operation between different people.